THE METHOD OF CALCULATION OF COEFFICIENTS OF THE PHASE ABERRATIONS OF AXIALLY ASYMMETRIC DUAL REFLECTOR ANTENNAS - B. N. Laskin; E. A. Bolelov (Научный вестник МГТУ ГА)
Aerodrome-enroute surveillance radar systems (ARSR) of civil aviation are designed for detection of aerial objects and determination of their range and movement parameters. Meanwhile, the reflector-type antennas are still the main type of_used antenna systems. Radars (ARSR) have, as a rule, antennas with a bidirectional beam, structurally reflector-type antenna is made in the form of a truss welded structure. The use of active phased antenna arrays (APAR) is a promising direction of radars (ARSR) development. Radars (ARSR) based on the phased antenna arrays can significantly improve such critical tactical and technical criteria as: the accuracy of the coordinates determination, the number of simultaneously followed targets. However, the use of APAR does not solve one of the main problems - the presence of a support-rotary device in the radar (ARSR). The principal necessity of a support-rotary device leads to the need of the use of movable joints of feeder lines, which, with a significant number of antenna elements used in the PAR, significantly reduces the potential time before failure. It seems promising to use in the radar antenna systems based on several stationary multi-beam dual-reflector antennas made by axially asymmetric scheme. Methodology of estimation of aberrations of a dual-reflector sensimetrics antenna based on a polynomial expansion of the eikonal function in the plane of the aperture of the main reflector is proposed in the article. Analytical expressions of the functions of display and rotation of the scanning plane of a dual-reflector axially asymmetric antenna with arbitrary parameters, designed based on clippings from centrally symmetric surfaces of rotation of the second order, are obtained. It is shown that the aplanatic antennas lose their scanning features during the transition to the axially asymmetric variant.